Relayout Lantai Produksi Tenda Guna Meminimasi Jarak Perpindahan Material - Berlian, Devin Agni; Wati, Putu Eka Dewi Karunia (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
CV. XYZ is a tent manufacturing company based in Surabaya facing issues with its production facility layout, which does not follow the actual production flow. This results in long material handling distances and inefficient workflow. This study aims to redesign the layout to minimize material movement distances and optimize space utilization. The methods used include observation, interviews, the creation of an Operation Process Chart, Multi Product Process Chart, From-To Chart, Systematic Layout Planning analysis, and simulation using FlexSim software. The research sample includes all workstations on the production floor of CV. XYZ. The results show that proposed layout 2 reduces the Material Handling burden by 29.01% and increases space utilization from 46.52 m² to 88.55 m². It is recommended that the company implement the proposed layout to enhance production efficiency.